pk001748: Peace Committee of Turkey
"Prentbriefkaart in zwart-wit voorstellend een kooi waarin een vogeltje gevangen zit. Tekst : Stop the trial of members of the peace committee of Turkey. Tekst op keerzijde : I join thousands of men and women dedicated to the cause of peace all over the world demanding - an immediate withdrawal of the prosecution and trial of leading members of the Peace Committee of Turkey, - the lifting of the ban on the activities of the Peace Committee of Turkey. Geadresseerd aan Gen. Kenan Evren, President of the Republic, Ankara, Turkey. FULL TEXT AVAILABLE AT AMSAB-ISH"